PROTOTYPE NURSE CALL WIRELESS FOR COVID-19 HOSPITAL PATIENT SERVICES - fredho, Gabriel; Pontia, F. Trias; Putra, Leonardus Sandy Ade (Faculty of Engineering, Universitas Tanjungpura, 2024)
The role of technology has a positive impact on companies or institutions, which allows companies to implement all functions within the company more quickly and easily. The use of technology in health services increases efficiency in hospitals with hospital services having to be faster, friendlier and more accurate. Some services in hospitals require the role of technology so that hospital services for patients can be handled more quickly, namely requiring technology that is able to monitor and treat inpatients. Improving services performed by hospitals and speeding up response times by using technology in patient calling. Currently, the development of nurse call bells has also been seen in hospitals as a form of effort to increase the response time of nurses in providing services to patients. The purpose of this research is to build a system that can make it easier for Covid 19 patients to call nurses, and make it easier for nurses to find Covid 19 patients who need action. The design uses Arduino Nano with LoRa communication. The system created refers to Covid-19 patients who need action. There are 3 indicators that patients can choose, namely emergency action, moderate action and usual action. This system is in the form of an indicator light aimed at the nurse on duty in the nurse control room. The test results of the wireless nurse call prototype were carried out with several variations, where when the condition without obstruction walls (LOS) the prototype worked within a maximum range of 40 meters. Under the condition of being given an obstacle (NLOS) of 1 obstacle wall, the prototype works within a maximum range of 35 meters. Whereas with the condition of being given a barrier (NLOS) of 2 obstacle walls, the prototype works within a maximum range of 30 meters. So that the condition of the distance between the nurse's control room and the patient's room affects the performance of the Nurse Call Wireless prototype.